2024
DOI: 10.3390/agronomy14020299
|View full text |Cite
|
Sign up to set email alerts
|

Excavation of Genes Response to Heat Resistance by Transcriptome Analysis in Bottle Gourd (Lagenaria siceraria (Mol.) Standl.)

Min Wang,
Wenrui Liu,
Qingwu Peng
et al.

Abstract: Heat stress, as a negative factor, severely threatens the quality and production of bottle gourd, which prefers to grow in a warm environment. To understand which genes are involved in the resistance to heat stress in bottle gourd (Lagenaria siceraria (Mol.) Standl.), we analyzed the characteristics of two genetic bottle gourd varieties, “Mei feng”-MF (heat resistant) and “Lv long”-LL (heat sensitive). Under heat stress, MF plants exhibited a higher survival rate, lower relative electrolytic leakage, and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The transcriptome analysis conducted in the study revealed some key genes that may be related to plant heat resistance, providing new research ideas for the future improvement of heat-resistant vegetable varieties and a fresh perspective on the molecular mechanisms of plant heat resistance. The study provides an important foundation for coping with the challenge of heat stress caused by climate change [13].…”
mentioning
confidence: 99%
“…The transcriptome analysis conducted in the study revealed some key genes that may be related to plant heat resistance, providing new research ideas for the future improvement of heat-resistant vegetable varieties and a fresh perspective on the molecular mechanisms of plant heat resistance. The study provides an important foundation for coping with the challenge of heat stress caused by climate change [13].…”
mentioning
confidence: 99%